2022
DOI: 10.1111/poms.13658
|View full text |Cite
|
Sign up to set email alerts
|

How does warfare affect firms' productivity?

Abstract: Warfare afflicts millions and creates unparalleled operational challenges in the developing world. With data from war‐torn Colombia, I examine the effects of civil war on firms' total factor productivity (TFP) using propensity score and conflict hotspot models. I find that warfare increases TFP in service firms, such as public administration and defense, by up to 12.68%, whereas it decreases TFP in manufacturing and other nonservice companies by up to 3.64% a year after a violent episode occurs. This effect st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 64 publications
(151 reference statements)
0
2
0
Order By: Relevance
“…The TFP in these two methods is denoted as TFP_LP and TFP_OP , respectively. Both methods are widely used in economics and management literature to calculate firm productivity levels (e.g., Liu and Mao, 2019; Jola-Sanchez, 2022). Briefly, both methods are introduced by considering a Cobb–Douglas production function, as presented below:…”
Section: Methodsmentioning
confidence: 99%
“…The TFP in these two methods is denoted as TFP_LP and TFP_OP , respectively. Both methods are widely used in economics and management literature to calculate firm productivity levels (e.g., Liu and Mao, 2019; Jola-Sanchez, 2022). Briefly, both methods are introduced by considering a Cobb–Douglas production function, as presented below:…”
Section: Methodsmentioning
confidence: 99%
“…This line of work has focused on two aspects of OM during major crises. The first examines how disasters affect small business operations, such as operational performance and supply chain capacity (e.g., Hendricks et al, 2020;Jola Sanchez, 2022). In a study particularly relevant to our theme, Alekseev et al (2023) studied small businesses during the COVID-19 pandemic and found that they faced financial challenges and had limited access to funding.…”
Section: Disaster Management and Small Businessesmentioning
confidence: 99%